2011
DOI: 10.1097/mca.0b013e3283472a57
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D levels and vitamin D receptor polymorphisms in relation to coronary artery disease

Abstract: Low vitamin D level was associated with an enhanced risk for incident CAD. VDR genotypes did not show any association with either vitamin D levels or CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
2
18
0
2
Order By: Relevance
“…Ortlepp et al determined an association between the G/G genotype of VDR gene BsmI polymorphism and the risk of myocardial infarction in patients under the age of 65 [31]. The contradictory data were obtained by Shanker et al [32] and Pan et al [33] -they detected no association between polymorphic variants and haplotypes of the VDR gene and the development of coronary heart disease. Porojan et al examined the relation of VKORC1 allelic polymorphisms with atherosclerosis and calci- fi cation.…”
Section: Resultsmentioning
confidence: 86%
“…Ortlepp et al determined an association between the G/G genotype of VDR gene BsmI polymorphism and the risk of myocardial infarction in patients under the age of 65 [31]. The contradictory data were obtained by Shanker et al [32] and Pan et al [33] -they detected no association between polymorphic variants and haplotypes of the VDR gene and the development of coronary heart disease. Porojan et al examined the relation of VKORC1 allelic polymorphisms with atherosclerosis and calci- fi cation.…”
Section: Resultsmentioning
confidence: 86%
“…In the Korean Longitudinal Study on Health and Aging [17], low 25-OH vitamin D levels were associated with an increased prevalence of a more than 50% coronary artery stenosis as determined by cardiac CTA. In two separate Indian studies of individuals with angiographically proven coronary artery disease [19,20], those with vitamin D deficiency had a significantly higher prevalence of coronary artery stenoses. In contrast to these findings, in the previously mentioned Danish crosssectional study of type II diabetics with an elevated urinary albumin excretion rate [13], neither moderate (5.0-10.0 ng/ml) nor insufficient (10.0-20.0 ng/ml) vitamin D levels were significantly associated with an increased prevalence of significant coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the involvement of these biological processes in atherosclerosis. Abnormal vascular smooth muscle cell proliferation has been shown to increase the production of acute-phase reactant proteins like CRP, while Vitamin D deficiency has been implicated in cardiovascular disease [70][72]. Both TLR and NLR signaling pathways belong to a specific family of pattern recognition receptors that trigger the expression of several genes involved in innate immune response [73].…”
Section: Discussionmentioning
confidence: 99%